Multiple Myeloma Market Will Expand With Launch of Monoclonal Antibodies - Fellner, Chris (P T, 2016)
Analysts foresee substantial growth in the multiple myeloma market in the next decade, driven mainly by the monoclonal antibodies elotuzumab and daratumumab.